PREFERENSI SISWA SMA KELAS 11 TERHADAP PENGGUNAAN PAPAN TULIS DI ERA DIGITAL DAN IMPLIKASINYA TERHADAP KETERLIBATAN BELAJAR - Hanan Dimas Prasetya (Jurnal Riset Daerah, 2025)
In the digital era, educational technology is widely adopted to support student learning. However, recent classroom observations indicate that some Generation Z students may be more engaged during lessons that utilize traditional teaching tools, such as the physical chalkboard or whiteboard. This creates a paradox between the presumed digital preference of Gen Z learners and their actual classroom focus and engagement. This study aims (1) to identify and measure the preferences of 11th-grade Generation Z students regarding the use of physical whiteboards versus digital instructional media; (2) to explore the underlying factors behind their preferences; and (3) to analyze the implications of these preferences for student learning engagement. This research employed a mixed-method approach, combining quantitative Likert-scale questionnaires with qualitative interviews involving students and educators. The Wilcoxon Signed Ranks Test was used to compare preference scores between whiteboard-based and digital-based learning. Thematic analysis was applied to qualitative data to explore students' reasoning and experiences. The quantitative results revealed a significant preference for whiteboard use over digital media (p = 0.002). Most students reported increased focus and better understanding when the teacher used the board in a step-by-step manner. Qualitative findings supported these results, highlighting that whiteboards allow for a more synchronized learning rhythm, spontaneous interaction, and a sense of shared cognitive process between teacher and student. Despite being digital natives, Gen Z students in this study demonstrated a strong appreciation for the pedagogical value of traditional whiteboards. The findings suggest that combining digital tools with physical board usage offers a balanced approach that enhances focus and engagement. Educators are encouraged to integrate both tools to align with students’ cognitive needs and learning behaviors in the digital age.